Violating Labour’s Rights, A Failure Understanding Establishment of SOEs Holdings: Evidence at the State-owned Enterprise Cement Holding of PT Semen Indonesia (Persero) Tbk - Subiyanto, Effnu (Technium Social Sciences Journal, 2020)
This research aims due to disclose many phenomena that against with leadership’s theories. There are wide gap between capacities and capabilities of board of directors (BOD) and or board of commissioners (BOC) in terms understanding labour’s right and obligations. Lack of these understandings have triggered conflicts and disputes and drive to the mass demonstrations in the country. The methodology presented is event case study and mixed of quantitative and qualitative to build scientific research arguments. It found that violating labour’s welfares have proven occurred in the State-owned cement holding of PT Semen Indonesia since 2012 and therefore requiring academic advocating supports worldwide. These phenomenon are quite significant due to generally social behaviour in Indonesia, when none have risen consents and or delivered critics then the conditions are becoming normal, common, and legal. The most important is labour’s right and or labour’s welfare must be defended according destiny of human being and in accordance with regulations applied.